Vybrané závažné „hematologické“ syndromy u dospělých pacientů v intenzivní péči - Gumulec, Jaromír; Demel, Ivo; Lančová, Klára; Drbohlavová, Eva; Piegzová, Alicia; Kořístek, Zdeněk; Navrátil, Milan; Černý, Vladimír (Vnitrni lekarstvi, 2022)
Haemophagocytic syndrome, diffuse alveolar haemorrhage, catastrophic antiphospholipid syndrome and various types of thrombotic microangiopathies are rare conditions with significant morbidity and mortality. A common feature is late diagnosis, which can affect the success of treatment. The aim of this review article is to summarize the basic diagnostic and therapeutic steps of the present subpopulation of critically ill patients.
Keywords: rituximab; diffuse alveolar haemorrhage; thrombotic thrombocytopenic purpura; vasculitis; plasma exchange; ravulizumab; trombotické mikroangiopatie; haemolytic‑uremic syndrome; Antiphospholipid Syndrome; hemophagocytic lymphohistiocytosis; Humans; hemophagocytic syndrome; dospělí; recombinant factor VIIa; thrombosis; etoposide; HLH; caplacizumab; Lymphohistiocytosis, Hemophagocytic; lidé; Lens-Associated Uveitis; anti‑glomerular basement membrane (anti‑GBM) antibodies; antiphospholipid syndrome; cytokine storm syndrome; thrombotic microangiopathy; eculizumab; immunosuppressive therapy; antifosfolipidový syndrom; Adult; macrophage activation syndrome; lymfohistiocytóza hemofagocytární; catastrophic antiphospholipid syndrome; thrombotic microangiopathies; Thrombotic Microangiopathies